HUKUMAN TERHADAP ANAK SEBAGAI ALAT PENDIDIKAN DITINJAU DARI HUKUM ISLAM - Khomsiyah, Indah (IAIN Tulungagung, 2014)
Punishment is a severe physical action by person(s) from highstratum to the person(s) of lower stratum which is commonlyintended to show off the power. In the context of education,punishment is done to students to make them realize theirmistake and so, they do not make the same mistake in future.However, according to the teaching of Islam, punishment mustnot be conducted to children unless they make mistake and it isconducted evenly so that it does not remain on physical suffer.Punishment may only be done to make children learn Islambetter.Kata kunci: Hukuman, Pendidikan Anak, Hukum Islam